2013
DOI: 10.1093/treephys/tpt093
|View full text |Cite
|
Sign up to set email alerts
|

The effects of defoliation on carbon allocation: can carbon limitation reduce growth in favour of storage?

Abstract: There is no consensus about how stresses such as low water availability and temperature limit tree growth. Sink limitation to growth and survival is often inferred if a given stress does not cause non-structural carbohydrate (NSC) concentrations or levels to decline along with growth. However, trees may actively maintain or increase NSC levels under moderate carbon stress, making the pattern of reduced growth and increased NSCs compatible with carbon limitation. To test this possibility, we used full and half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
112
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(133 citation statements)
references
References 65 publications
16
112
2
Order By: Relevance
“…3), the increment from the first period was determined by amount of synthesised secondary metabolites rather than leaf damage, which was low at the time. It is likely that amount of assimilative organs loss affects growth of saplings like in Wiley et al (2013). Furthermore, the leaf damage caused a slight decrease in stem volume increment when its dynamics took place later.…”
Section: Discussionmentioning
confidence: 99%
“…3), the increment from the first period was determined by amount of synthesised secondary metabolites rather than leaf damage, which was low at the time. It is likely that amount of assimilative organs loss affects growth of saplings like in Wiley et al (2013). Furthermore, the leaf damage caused a slight decrease in stem volume increment when its dynamics took place later.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that even under severe stress conditions, C reserves are never fully depleted (Gruber et al 2012;Hartmann et al 2013;Klein et al 2014) and that reserve storage may, in certain cases, be favored at the expense of growth (Wiley et al 2013;Saffell et al 2014). Recent studies have demonstrated that, within a given growing season, the formation of C reserves occurs earlier in mature trees compared to young trees in experiments conducted under the same pedoclimatic conditions and leaf phenology (Gilson et al 2014).…”
Section: The Phenology Of Carbon and Nitrogen Reservesmentioning
confidence: 99%
“…carbon supply (photosynthesis) and carbon demand (respiration, growth or export) (Smith and Stitt, 2007;Sala et al, 2012;Dietze et al, 2014;Wiley et al, 2013). Any factor affecting carbon supply and demand would inevitably influence the carbon dynamics of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Attributes of non-structural carbohydrate storages are assumed to be an important life history trait (Canham et al, 1999;Gleason and Ares, 2004;Dietze et al, 2014). Recent studies have discovered that plants with higher NSC storages in leaves, stems or roots have a stronger ability to survive under drought stress (Adams et al, 2009(Adams et al, , 2013O'Brien et al, 2014O'Brien et al, , 2015, reduced light (Myers and Kitajima, 2007) and defoliation (Wiley et al, 2013). Additionally, NSC is actively maintained for signaling among cells and tissues (Lalonde et al, 1999;Smeekens, 2000;Smith and Stitt, 2007;Secchi and Zwieniecki, 2011).…”
Section: Introductionmentioning
confidence: 99%